Breeding for soil-borne pathogen resistance impacts active rhizosphere microbiome of common bean. Issue 12 (December 2018) - Mendes, Lucas; Mendes, Rodrigo; Raaijmakers, Jos; Tsai, Siu
Abstract Over the past century, plant breeding programs have substantially improved plant growth and health, but have not yet considered the potential effects on the plant microbiome. Here, we conducted metatranscriptome analysis to determine if and how breeding for resistance of common bean against the root pathogenFusarium oxysporum (Fox ) affected gene expression in the rhizobacterial community. Our data revealed that the microbiome of theFox -resistant cultivar presented a significantly higher expression of genes associated with nutrient metabolism, motility, chemotaxis, and the biosynthesis of the antifungal compounds phenazine and colicin V. Network analysis further revealed a more complex community forFox -resistant cultivar and indicatedPaenibacillus as a keystone genus in the rhizosphere microbiome. We suggest that resistance breeding in common bean has unintentionally co-selected for plant traits that strengthen the rhizosphere microbiome network structure and enrich for specific beneficial bacterial genera that express antifungal traits involved in plant protection against infections by root pathogens.